Tweet, Tweet, Retweet: Conversational Aspects of Retweeting on Twitter - boyd, danah; Golder, Scott; Lotan, Gilad (43rd Hawaii International Conference on Social Systems (HICSS), 2010)
Twitter—a microblogging service that enables users to post messages (“tweets”) of up to 140 characters—supports a variety of communicative practices; participants use Twitter to converse with individuals, groups, and the public at large, so when conversations emerge, they are often experienced by broader audiences than just the interlocutors. This paper examines the practice of retweeting as a way by which participants can be “in a conversation.” While retweeting has become a convention inside Twitter, participants retweet using different styles and for diverse reasons. We highlight how authorship, attribution, and communicative fidelity are negotiated in diverse ways. Using a series of case studies and empirical data, this paper maps out retweeting as a conversational practice.
Citation: boyd, danah, Scott Golder, and Gilad Lotan (Forthcoming, 2010)."Tweet Tweet Retweet: Conversational Aspects of Retweeting on Twitter." Proceedings of HICSS-42, Persistent Conversation Track. Kauai, HI: IEEE Computer Society. January 5-8, 2010.